Embelin-loaded guar gum microparticles for the management of ulcerative colitis. (17th February 2018) - Sharma, Ankita; Kaur, Navneet; Sharma, Saurabh; Sharma, Amit; Rathore, M. S.; Ajay, Kumar; Mishra, Neeraj
Abstract: The aim of the present study is to develop embelin-loaded guar gum microparticles through emulsification technique. The in vitro release of the optimised formulation was found to be 88.5 ± 3.8% in 24 h, has exhibited remarkably sustain and delayed the release of embelin at a specific site. Embelin-loaded microparticles showed average particle size of 12.9 ± 0.75 µm. The statistical analysis was carried out by one-way ANOVA followed by comparison test of Bonferroni. P values < 0.05 were considered as significant. The in vivo study concluded that pre-treatment of embelin prevents dinitrobenzenesulfonic acid (DNBS)-induced colitis in rats and depicts protective activity against ulcerative colitis due to its antioxidant and anti-inflammatory actions. This approach produces comparatively less side effect to another conventional dosage form.